Stacked connector electronic component
Patent Information
- Application Number
- CN202510661898.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-30
- Filing Date
- 2025-05-22
- Publication Date
- 2026-10-30
AI Technical Summary
然所述导电层仍很难完全阻止硫化因子侵入,因此表面电极中的银仍可能因硫化而生成硫化银
[0005]本发明的另一目的在于提供一种连接器电子元件,其可具有传输损耗低及可靠性佳的优点,进而提高包含其的电子设备的性能。
Smart Images

Figure CN123017605A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to connector electronic components used in electronic devices. Background Technology
[0002] Electronic ceramics encompass passive components such as multilayer ceramic capacitors, inductors, connectors, and resistors. Due to their small size, they are widely used in automotive, wearable devices, and mobile telecommunications. With the current demands and development of the communications industry, miniaturization and modularization of circuits have become a key research focus to meet the requirements of multifunctional and lightweight wireless communication modules. However, the continuous reduction in component size and the spacing between conductors increases the resistance and capacitance between metal conductors during signal transmission, leading to increased power consumption and signal exchange interference, thus causing signal sluggishness (RC sluggishness).
[0003] Furthermore, traditional thick-film connector electronic components typically employ printing or sputtering to coat the two ends of a ceramic substrate (e.g., alumina) with conductive materials (such as silver or silver-palladium alloys) to form internal electrodes. A resistive layer is then deposited on the upper surface of the substrate, connecting to the internal electrodes. Since electronic devices may use sulfur-containing materials or be used in sulfur-containing environments, the internal electrodes and resistive layer may combine with sulfurous gases to form electrically insulating silver sulfide (Ag₂S), leading to sulfidation and wire breakage in the thick-film connector electronic components. Therefore, thick-film connector electronic components typically require an insulating material to cover the resistive layer to form a protective layer, followed by a series of complex processes such as curing, laser trimming, folding, end electrode rolling, granulation, and electroplating. These methods are not only expensive and complex, but also prone to breakage during folding and granulation processes after component miniaturization, leading to decreased overall process yield, increased costs, and even component reliability degradation or failure. Furthermore, regarding the problem of sulfidation factor (water and sulfur) intrusion, Japanese Patent Application Publication No. JP2007123832A discloses a technical solution that mainly utilizes a specific resin-based conductive coating to form a conductive layer on the surface of a surface electrode (a silver-containing metallic glaze). However, the conductive layer is still difficult to completely prevent sulfidation factor intrusion, so the silver in the surface electrode may still form silver sulfide due to sulfidation. Summary of the Invention
[0004] In view of the technical defects of the above-mentioned connector electronic components, the purpose of this invention is to provide a connector electronic component that can simplify the manufacturing process and reduce costs, thereby increasing the diversity of subsequent applications, such as being more in line with the requirements of automotive qualified products.
[0005] Another object of the present invention is to provide a connector electronic component that has the advantages of low transmission loss and high reliability, thereby improving the performance of electronic devices containing it.
[0006] To achieve the aforementioned objective, the present invention provides a multilayer connector electronic component, comprising: a ceramic body having a first end face and a second end face opposite to each other; and two electrodes respectively covering the first end face and the second end face of the ceramic body; wherein the ceramic body is formed by sequentially stacking a ceramic upper cover layer, a ceramic electrode layer, and a ceramic lower cover layer; the ceramic electrode layer includes a plurality of ceramic sublayers and a first interconnect electrode stack, the first interconnect electrode stack including a plurality of metal conductive layers, the ceramic sublayers and the metal conductive layers... The layers are alternately stacked and sandwiched between the upper ceramic cover layer and the lower ceramic cover layer, and the metal conductive layer is electrically connected to the two-terminal electrodes; wherein, the ceramic material forming the upper ceramic cover layer, the ceramic sublayer and the lower ceramic cover layer comprises a main powder material and a sintering aid, the main powder material comprises a silicate-based microwave dielectric material, a barium titanate-based microwave dielectric material, calcium zirconate (CaZrO3), a strontium zirconate titanate compound or a combination thereof, wherein the molar ratio of barium to titanium contained in the barium titanate-based microwave dielectric material is less than 1; the metal conductive layer comprises a base metal.
[0007] This invention, by selecting a specific main powder material with low dielectric constant (k) and low dielectric loss (tanδ), reduces parasitic capacitance induced with adjacent wires and the formation of a low-resistivity metallic conductive layer, thus mitigating RC lag. Furthermore, ceramics possess high insulation resistance, thereby improving current carrying capacity. Moreover, the multilayer structure of alternating ceramic sublayers and multiple metallic conductive layers provides excellent bending resistance for the multilayer connector electronic components, significantly reducing the risk of failure due to open circuits when subjected to external stress. Additionally, since the ceramic body is formed by stacking multiple ceramic sublayers, it achieves densification through debonding and sintering. After end electrode sintering, it prevents the intrusion of moisture and sulfide gases (H2S, SO2, etc.), reducing load-life inhumidity and the risk of sulfide-induced wire breakage, thereby improving process yield. In addition, since this invention does not require the use of precious metal raw materials, it can also reduce manufacturing costs.
[0008] Preferably, the base metal may comprise copper (Cu), nickel (Ni), or a combination thereof.
[0009] According to the present invention, the conductive metal layer can be formed from an electrode layer composition. In some embodiments, the electrode layer composition comprises base metal powder, ceramic powder, a base resin, and a solvent. In some embodiments, the conductive metal layer can be formed by printing the electrode layer composition onto the surface of a ceramic sublayer, but is not limited thereto. In other embodiments, the conductive metal layer can be formed by printing the electrode layer composition onto the inner surface of the ceramic top cover layer, but is not limited thereto.
[0010] Preferably, the average particle size of the base metal powder is 0.1 micrometers (μm) to 1 μm; the average particle size of the ceramic powder is 0.01 μm to 1 μm; the aforementioned average particle size is the particle size D measured by laser diffraction particle size distribution method. 50 What is represented.
[0011] Preferably, the base metal powder is copper powder or nickel powder. The ceramic powder may contain BaTiO3, BaTi4O9, (SrCa)(ZrTi)O3, CaZrO3, or combinations thereof, but is not limited thereto. The base resin may contain ethylcellulose resin, but is not limited thereto. The solvent may contain terpineol, hydrogenated terpineol, benzyl alcohol, 2-ethyl-1-hexanol, 1-octanol, or combinations thereof, but is not limited thereto.
[0012] Preferably, based on the total weight of the electrode layer composition, the content of the base metal powder is from 34.5 wt% to 55.5 wt%; the content of the ceramic powder is from 0 wt% to 15.5 wt%; the content of the base resin is from 1.2 wt% to 2.3 wt%; and the content of the solvent is from 40.0 wt% to 51.5 wt%.
[0013] Preferably, the ceramic materials forming the ceramic upper cover layer, the ceramic sub-layers, and the ceramic lower cover layer can all be the same; that is, the ceramic materials forming the ceramic upper cover layer, the ceramic sub-layers, and the ceramic lower cover layer are all the same. However, this invention does not preclude the possibility that the ceramic materials forming each layer can be independently selected from embodiments that conform to the raw material types defined in this invention. For example, in some embodiments, the ceramic materials forming the ceramic upper cover layer and the ceramic lower cover layer are the same, but different from the ceramic materials forming the ceramic sub-layers, but this is not a limitation.
[0014] Preferably, the silicate-based microwave dielectric material may contain Mg2SiO4, Zn2SiO4, MgCaSi2O6 or combinations thereof, but is not limited thereto.
[0015] Preferably, the molar ratio (Ba / Ti) of barium to titanium in the barium titanate-based microwave dielectric material is between 0.200 and 0.286. Specifically, the barium titanate-based microwave dielectric material may contain BaTi4O9 (i.e., Ba / Ti = 0.250) or Ba2Ti9O9. 20 (i.e., Ba / Ti = 0.222) or combinations thereof, but not limited to these.
[0016] Preferably, the strontium zirconate titanate compound can be represented by formula (1):
[0017] (SraCabBac)(ZrxTiy)O3(1);
[0018] wherein 0<a<1, 0<b<1, 0≤c<1, a+b+c=1; 0<x<1, 0<y<1, x+y=1.
[0019] In some embodiments, 0<a<0.5, 0.5≤b<1, c=0, a+b+c=1. In other embodiments, 0<a<0.5, 0.5≤b<0.9, 0<c<0.1, a+b+c=1.
[0020] Specifically, the strontium zirconate titanate-based compound may comprise (Ca 0.7 Sr 0.3 )(Zr 0.96 Ti 0.04 )O3, (Ca 0.68 Sr 0.32 )(Zr 0.9 Ti 0.1 )O3, (Ca 0.68 Sr 0.32 )(Zr 0.66 Ti 0.34 )O3, (Sr 0.14 Ca 0.82 Ba0.04)(Zr 0.46 Ti 0.54 )O3 or a combination thereof, but is not limited thereto.
[0021] Preferably, based on the solid content of the ceramic material, the total solid content of the main powder material may be 60 wt% to 70 wt%, but is not limited thereto.
[0022] Preferably, the ceramic material may further comprise a sintering aid, which can reduce the sintering temperature of the ceramic material. In some embodiments, the sintering aid may comprise a glass material; for example, the glass material may comprise Li2O-BaO-SrO-CaO-B2O3-SiO2, Na2O-BaO-ZnO-B2O3-Al2O3-SiO2-CaO, MnO-MgO-Al2O3-SiO2, BaO-MgO-Al2O3-SiO2, CaO-Al2O3-SiO2, BaO-ZnO-B2O3-CaO-Al2O3-SiO2-Cu2O, Na2O-BaO-ZnO-B2O3-Al2O3-SiO2, Na2O-BaO-ZnO-B2O3-CaO-Al2O3-SiO2-Cu2O or a combination thereof, but is not limited thereto. Preferably, the glass material may be in the form of powder particles, and may have an average particle size of 0.1 μm to 3.0 μm, but is not limited thereto.
[0023] Preferably, with a total weight of 100 parts by weight for the main powder material and the sintering aid, the content of the sintering aid may be greater than 0 parts by weight and less than or equal to 15 parts by weight, but is not limited thereto. More preferably, with a total weight of 100 parts by weight for the main powder material and the sintering aid, the content of the sintering aid may be from 1 part by weight to 12 parts by weight, but is not limited thereto.
[0024] In some embodiments, when the base metal of the metal conductive layer is copper, and the ceramic material comprises the silicate-based microwave dielectric material and the glass material, the glass material may be Li2O-BaO-SrO-CaO-B2O3-SiO2; preferably, with the total weight of the main powder material and the glass material being 100 parts by weight, the content of the glass material may be 8 to 10 parts by weight.
[0025] In some embodiments, when the base metal of the conductive metal layer is copper and the ceramic material comprises the calcium zirconate and the glass material, the glass material may be MnO-MgO-Al2O3-SiO2; preferably, with the total weight of the main powder material and the glass material being 100 parts by weight, the content of the glass material may be 8 to 10 parts by weight.
[0026] In some embodiments, when the base metal of the conductive metal layer is copper, and the ceramic material comprises the barium titanate microwave dielectric material and the glass material, the glass material may be Na2O-BaO-ZnO-B2O3-CaO-Al2O3-SiO2-Cu2O; preferably, with a total weight of 100 parts by weight for the main powder material and the glass material, the content of the glass material may be 8 to 10 parts by weight.
[0027] In some embodiments, when the base metal of the conductive metal layer is copper, and the ceramic material comprises the strontium titanate compound and the glass material, the glass material may be MnO-MgO-Al2O3-SiO2; preferably, with the total weight of the main powder material and the glass material being 100 parts by weight, the content of the glass material may be 10 to 12 parts by weight.
[0028] In some embodiments, when the base metal of the conductive metal layer is nickel, and the ceramic material comprises the strontium titanate compound and the glass material, the glass material may be MnO-MgO-Al2O3-SiO2; preferably, with a total weight of 100 parts by weight for the main powder material and the glass material, the content of the glass material may be 1 to 3 parts by weight.
[0029] Preferably, the ceramic material may further comprise a dispersant; for example, the dispersant may comprise an acrylic copolymer having pigment-affinity groups; for example, the dispersant may be a commercially available product (manufacturer: BYK, model: DISPERBYK-2001), but is not limited thereto. Preferably, based on 100 parts by weight of the total weight of the main powder material and the sintering aid, the content of the dispersant may be 3 to 4 parts by weight, but is not limited thereto.
[0030] Preferably, the ceramic material may further comprise a binder; for example, the binder may comprise polyvinyl butyral resin, (meth)acrylic resin, or a combination thereof, but is not limited thereto. Preferably, based on 100 parts by weight of the total weight of the main powder material and the sintering aid, the binder content may be from 10.5 parts by weight to 13.5 parts by weight, but is not limited thereto.
[0031] Preferably, the ceramic material may further comprise a plasticizer; for example, the plasticizer may comprise phthalates (PAEs); specifically, the phthalates may comprise: bis(2-ethylhexyl)phthalate (DEHP), dibutylphthalate (DBP), diisononylphthalate (DINP), butyl benzylphthalate (BBP), and di-isodecyl phthalate (DIDP), but are not limited thereto. Preferably, based on 100 parts by weight of the main powder material and the sintering aid, the content of the plasticizer may be 1.5 parts by weight to 2.5 parts by weight, but is not limited thereto.
[0032] Preferably, the ceramic material can be mixed with an organic solvent to form a ceramic slurry, which is then coated to form the ceramic layers (i.e., the ceramic upper layer, the ceramic sublayer, and the ceramic lower layer), but is not limited thereto. Specifically, the organic solvent may contain toluene, ethanol, or a combination thereof, but is not limited thereto. Preferably, the organic solvent may be a combination of toluene and ethanol, and the weight ratio of toluene to ethanol may be 6:4 to 4:6; for example, the weight ratio of benzene to ethanol may be 5:5.
[0033] Preferably, the dielectric constant (k) of the ceramic material at 1 MHz is less than 100, and the dielectric loss factor (tanδ) of the ceramic material at 1 MHz is less than 0.001.
[0034] Preferably, at a test voltage of 50V, the insulation resistance (IR) of the ceramic material is greater than 5*10⁹ Ω. More preferably, the insulation impedance of the ceramic material is greater than 5*10¹⁰ Ω.
[0035] Preferably, the Young's modulus (E) of the ceramic material is greater than 90 GPa, but is not limited thereto; more preferably, the Young's modulus of the ceramic material is between 130 GPa and 220 GPa. Preferably, the hardness (H) of the ceramic material is between 6.7 GPa and 13 GPa, but is not limited thereto. The aforementioned Young's modulus and hardness are obtained from the load-depth curve of the ceramic material sample during the indentation process using a nanoindenter measurement system according to JIS R1607 and JIS R1610 standards; wherein the indenter displacement resolution is less than 0.01 nm, the maximum indentation depth is 500 μm, and the maximum indentation load is 500 mN. Preferably, the (E / H)1 / 2 value of the ceramic material is greater than 4, but is not limited thereto.
[0036] Preferably, the average thickness of the ceramic upper cover layer can be from 5 μm to 40 μm, but is not limited thereto. Preferably, the average thickness of the ceramic lower cover layer can be from 10 μm to 25 μm, but is not limited thereto.
[0037] Preferably, the total thickness of the ceramic electrode layer can be from 80 μm to 190 μm, but is not limited thereto. Preferably, the average thickness of each ceramic sublayer can be from 1.25 μm to 10 μm, but is not limited thereto. Preferably, the average thickness of each metal conductive layer can be from 1.0 μm to 20 μm, but is not limited thereto. In some embodiments, the average thickness of the ceramic top cover layer, the average thickness of the ceramic bottom cover layer, and the average thickness of each ceramic sublayer are all the same. In other embodiments, the average thickness of each ceramic sublayer is the same, but the average thickness of the ceramic sublayer is not the same as the average thickness of the ceramic top cover layer and the average thickness of the ceramic bottom cover layer. In some embodiments, the number of ceramic sublayers contained in the ceramic electrode layer can be from 7 to 55, but is not limited thereto.
[0038] Optionally, the thickness ratio of each metal conductive layer to each ceramic sublayer is from 0.1 to 0.95, but is not limited thereto. Preferably, the thickness ratio of each metal conductive layer to each ceramic sublayer is from 0.28 to 0.9. When the thickness ratio of each metal conductive layer to each ceramic sublayer included in the multilayer connector electronic component of the present invention is within the aforementioned range, the multilayer connector electronic component has better bending failure resistance (i.e., a lower value).
[0039] In some embodiments, each terminal electrode may have a double-layer structure, meaning that each terminal electrode comprises a first sub-terminal electrode and a second sub-terminal electrode from the inside out. The first sub-terminal electrode covers the first and second end faces of the ceramic body and is electrically connected to the metal conductive layer. The second sub-terminal electrodes are formed on the outer surface of the first sub-terminal electrode. The aforementioned second sub-terminal electrodes provide protection, thus further improving the reliability of the multilayer connector electronic components. In some embodiments, the first sub-terminal electrode may contain copper, and the second sub-terminal electrode may contain nickel.
[0040] In some embodiments, the end electrode can be formed from an end electrode paste; specifically, it is formed by applying the electrode paste to the first end face and the second end face of the ceramic body and performing a sintering step, but is not limited thereto. In some embodiments, the end electrode paste contains conductive particles, a sintering aid, a resin, and an electrode paste solvent. In some embodiments, the end electrode paste can form two first sub-end electrodes and / or two second sub-end electrodes, but is not limited thereto. In other embodiments, the end electrode can be formed by electroplating or sputtering a metal layer (e.g., a second sub-end electrode); the aforementioned metal layer can be a copper layer or a nickel layer, but is not limited thereto.
[0041] Preferably, in the terminal electrode paste, the average particle size of the conductive particles is 0.5 μm to 5 μm; the aforementioned average particle size is the particle size D measured by laser diffraction particle size distribution method. 50 As indicated. In some embodiments, the conductive particles contained in the terminal electrode paste may have different sizes, for example: the conductive particles may include copper powder with an average particle size of 0.5 μm to 1 μm and copper powder with an average particle size of 2.0 μm to 4.0 μm.
[0042] Preferably, the conductive particles are copper powder or nickel powder. Preferably, the sintering aid may contain glass powder, which may be B2O3-BaO-ZnO based glass, but is not limited thereto. The resin may contain acrylic resin, but is not limited thereto. The electrode paste solvent may contain terpineol, hydrogenated terpineol, benzyl alcohol, 2-ethylhexanol, n-octanol, or combinations thereof, but is not limited thereto.
[0043] Preferably, based on the total weight of the terminal electrode paste, the content of the conductive particles is 78.5 wt% to 83.5 wt%; the content of the sintering aid is 9 wt% to 11 wt%; the content of the resin is 4.25 wt% to 5.75 wt%; and the content of the electrode paste solvent is 3.25 wt% to 4.75 wt%.
[0044] In some embodiments, the multilayer connector electronic component further includes two solder layers that respectively cover the outer surfaces of the two terminal electrodes. That is, when each terminal electrode has a double-layer structure (i.e., having a first sub-terminal electrode and a second sub-terminal electrode), each solder layer covers a second sub-terminal electrode. Preferably, the two solder layers contain tin (Sn), but are not limited thereto. Preferably, each solder layer is formed on the outer surface of one terminal electrode by electroplating; in some embodiments, the aforementioned first sub-terminal electrode contains copper, and the aforementioned second sub-terminal electrode contains nickel.
[0045] Preferably, the ceramic electrode layer may comprise multiple sets of interconnecting electrode stacks, and each set of interconnecting electrode stacks may comprise multiple conductive metal layers. The number of conductive metal layers in each set of interconnecting electrode stacks may be the same or different. Since the spacing between different sets of interconnecting electrode stacks is slightly larger than the spacing between conductive metal layers within the same set of interconnecting electrode stacks, the risk of failure due to open circuits can be further reduced when the connector electronic component of the present invention is damaged by external stress.
[0046] In some embodiments, when the ceramic electrode layer includes two sets of connecting electrode stacks, namely a first connecting electrode stack and a second connecting electrode stack, the first connecting electrode stack and the second connecting electrode stack are arranged side by side in the horizontal direction of the ceramic body when viewed from the first end face to the second end face. Preferably, the metal conductive layers contained in the first connecting electrode stack are the same as those contained in the second connecting electrode stack (the number of layers, thickness, material, etc. are all the same), and each metal conductive layer in the first connecting electrode stack is parallel to each metal conductive layer in the second connecting electrode stack, and they have a horizontal distance between them in the horizontal direction.
[0047] Alternatively, in other embodiments, when the ceramic electrode layer includes a first connecting electrode stack group and a second connecting electrode stack group, when viewed from the first end face of the ceramic body towards the second end face, the first connecting electrode stack group and the second connecting electrode stack group are arranged side by side in the vertical direction of the ceramic body; and the uppermost metal conductive layer in the second connecting electrode stack group and the lowermost metal conductive layer in the first connecting electrode stack group are parallel to each other and spaced apart by a predetermined distance in the vertical direction of the ceramic electrode layer, the predetermined distance being greater than the distance between each metal conductive layer in the first connecting electrode stack group. Preferably, the metal conductive layers contained in the first connecting electrode stack are the same as those contained in the second connecting electrode stack (the number of layers, thickness, material, etc. are all the same), and each metal conductive layer in the first connecting electrode stack is parallel to each other in the second connecting electrode stack. In the vertical direction, there is a predetermined distance between the lowest metal conductive layer in the first connecting electrode stack and the highest metal conductive layer in the second connecting electrode stack, and the predetermined distance is greater than the vertical distance between each metal conductive layer in the first connecting electrode stack.
[0048] In some embodiments, when the ceramic electrode layer includes three sets of connecting electrode stacks (i.e., the first to the third connecting electrode stacks), viewed from the first end face to the second end face of the ceramic body, the first to the third connecting electrode stacks are arranged sequentially side-by-side in the horizontal direction of the ceramic body. Preferably, the metal conductive layers included in the first connecting electrode stack are the same as those included in the second and third connecting electrode stacks (the number of layers, thickness, material, etc. are all the same), and each metal conductive layer in the first connecting electrode stack is parallel to each metal conductive layer in the second connecting electrode stack, and has a predetermined distance between them in the horizontal direction; each metal conductive layer in the second connecting electrode stack is parallel to each metal conductive layer in the third connecting electrode stack, and has a predetermined distance between them in the horizontal direction.
[0049] In some embodiments, when the ceramic electrode layer includes four sets of connecting electrode stacks (i.e., the first to the fourth connecting electrode stacks), viewed from the first end face to the second end face of the ceramic body, the first and second connecting electrode stacks are arranged side-by-side in the horizontal direction of the ceramic body, the third and fourth connecting electrode stacks are arranged side-by-side in the horizontal direction of the ceramic body, and the first and third connecting electrode stacks are arranged side-by-side in the vertical direction of the ceramic body. Preferably, the metal conductive layers contained in the first to the fourth connecting electrode stacks are all the same (the number of layers, thickness, material, etc. are all the same), but this is not limited to this.
[0050] In some embodiments, when the ceramic electrode layer includes six sets of connecting electrode stacks (i.e., the first to the sixth connecting electrode stacks), viewed from the first end face to the second end face of the ceramic body, the first to the third connecting electrode stacks are arranged side-by-side sequentially in the horizontal direction of the ceramic body, the fourth to the sixth connecting electrode stacks are arranged side-by-side sequentially in the horizontal direction of the ceramic body, and the first and fourth connecting electrode stacks are arranged side-by-side in the vertical direction of the ceramic body. Preferably, the metal conductive layers contained in the first to the sixth connecting electrode stacks are all the same (the number of layers, thickness, material, etc. are all the same), but this is not limited to this.
[0051] In some embodiments, when the ceramic electrode layer includes nine sets of connecting electrode stacks (i.e., the first to the ninth connecting electrode stacks), when viewed from the first end face to the second end face of the ceramic body, the first to the third connecting electrode stacks are arranged in parallel in the horizontal direction of the ceramic body, the fourth to the sixth connecting electrode stacks are arranged in parallel in the horizontal direction of the ceramic body, the seventh to the ninth connecting electrode stacks are arranged in parallel in the horizontal direction of the ceramic body, and the first, fourth, and seventh connecting electrode stacks are arranged in parallel in the vertical direction of the ceramic body. Preferably, the first to the third and seventh to the ninth interconnecting electrode stacks contain identical metal conductive layers (the number of layers, thickness, material, etc. are all the same); the fourth to the sixth interconnecting electrode stacks contain identical metal conductive layers (the number of layers, thickness, material, etc. are all the same); however, the number of metal conductive layers in the first interconnecting electrode stack is greater than the number of metal conductive layers in the fourth interconnecting electrode stack.
[0052] In some embodiments, when the ceramic electrode layer includes 12 sets of connecting electrode stacks (i.e., the first to the twelfth connecting electrode stacks), when viewed from the first end face to the second end face of the ceramic body, the first to the fourth connecting electrode stacks are arranged in parallel in the horizontal direction of the ceramic body, the fifth to the eighth connecting electrode stacks are arranged in parallel in the horizontal direction of the ceramic body, the ninth to the twelfth connecting electrode stacks are arranged in parallel in the horizontal direction of the ceramic body, and the first, fifth, and ninth connecting electrode stacks are arranged in parallel in the vertical direction of the ceramic body. Preferably, the first to fourth and ninth to twelfth connecting electrode stacks contain identical metal conductive layers (the number of layers, thickness, material, etc. are all the same); the fifth to eighth connecting electrode stacks contain identical metal conductive layers (the number of layers, thickness, material, etc. are all the same); however, the first connecting electrode stack contains more metal conductive layers than the fifth connecting electrode stack contains.
[0053] Furthermore, the manufacturing method of the multilayer connector electronic component of the present invention is not particularly limited.
[0054] The multilayer connector electronic component of the present invention can be applied to signal transmission in mobile phone communication modules, wireless network (Wi-Fi) modules, automotive communication modules, current sensors, etc., but is not limited thereto.
[0055] The present invention provides a multilayer connector electronic component applicable to any size, particularly suitable for use with micro-components, such as: 0.4±0.02 mm long × 0.2±0.02 mm wide × 0.13±0.02 mm thick; or, 0.4±0.02 mm long × 0.2±0.02 mm wide × 0.2±0.02 mm thick; or, 0.30±0.01 mm long × 0.15±0.01 mm wide × 0.13±0.01 mm thick, but not limited thereto.
[0056] In this specification, the range represented by "smallest value to largest value" means, unless otherwise specified, that the range is greater than or equal to the smallest value and less than or equal to the largest value. For example, an average particle size of 0.5 μm to 1 μm means that the average particle size range is "greater than or equal to 0.5 μm and less than or equal to 1 μm". Attached Figure Description
[0057] Figures 1A to 1CThe images are, in sequence, a cross-sectional view of the first embodiment of the multilayer connector electronic component of the present invention, a cross-sectional view of the ceramic body along section line 1B-1B, and a side end view of the ceramic body.
[0058] Figures 2A to 2C The images are, in sequence, a cross-sectional view of the second embodiment of the multilayer connector electronic component of the present invention, a cross-sectional view of the ceramic body along section line 2B-2B, and a side view of the ceramic body.
[0059] Figures 3A to 3C These are, in sequence, a cross-sectional view of the third embodiment of the multilayer connector electronic component of the present invention, a cross-sectional view of the ceramic body along section line 3B-3B, and a side view of the ceramic body.
[0060] Figures 4A to 4C These are, in sequence, a cross-sectional view of the fourth embodiment of the multilayer connector electronic component of the present invention, a cross-sectional view of the ceramic body along section line B-4B, and a side end view of the ceramic body.
[0061] Figures 5A to 5C These are, in sequence, a cross-sectional view of the fifth embodiment of the multilayer connector electronic component of the present invention, a cross-sectional view of the ceramic body along section line 5B-5B, and a side end view of the ceramic body.
[0062] Figures 6A to 6C These are, in sequence, a cross-sectional view of the sixth embodiment of the multilayer connector electronic component of the present invention, a cross-sectional view of the ceramic body along section lines 6B-6B, and a side end view of the ceramic body.
[0063] Figures 7A to 7C These are, in sequence, a cross-sectional schematic diagram of the seventh embodiment of the multilayer connector electronic component of the present invention, a cross-sectional schematic diagram of the ceramic body along section lines 7B-7B, and a side end view of the ceramic body.
[0064] Figures 8A to 8C These are, in sequence, a cross-sectional view of the eighth embodiment of the multilayer connector electronic component of the present invention, a cross-sectional view of the ceramic body along section line 8B-8B, and a side end view of the ceramic body.
[0065] Figure 9 This is a side cross-sectional view of the thick-film connector electronic component in Example 2. Detailed Implementation
[0066] The following examples and references illustrate the implementation of the present invention. Those skilled in the art can easily understand the advantages and effects of the present invention through the content of this specification, and can make various modifications and changes without departing from the spirit of the present invention to implement or apply the content of the present invention.
[0067] Examples 1 to 47 (E1 to E49): Simulated samples of ceramic electrode layers
[0068] Since the loss of the ceramic layer itself is also one of the important factors affecting the overall signal transmission loss of the connector electronic components, Examples 1 to 49 first use simplified ceramic electrode layer simulation samples to confirm the correlation between the type of ceramic material and signal propagation loss.
[0069] First, according to Table 1-1, in Examples 1 to 49, specific main powder materials and specific sintering aids were added to an organic solvent (a mixed solution of toluene and ethanol, with a weight ratio of 1:1) in specific proportions and mixed. Next, 3.5 ± 0.5 parts by weight of a dispersant (manufacturer: BYK, model: DISPERBYK-2001) was added to the organic solvent to form a first mixture. Subsequently, after grinding and dispersing the first mixture, 12 ± 1.5 parts by weight of a binder (polyvinyl butyral resin) and 2 ± 0.5 parts by weight of a plasticizer (DEHP) were added and thoroughly stirred to form a ceramic slurry. Then, the ceramic slurry was coated to form multiple ceramic strips with a thickness of 30 μm. Next, about 10 ceramic strips are stacked one on top of the other to form a cylindrical blank and a pressure equalization step is performed. Then, an electrode layer composition (containing argon metal powder) is coated on the upper and lower surfaces of the cylindrical blank, followed by a debinding step and a sintering step. Finally, a simulated sample of a cylindrical ceramic electrode layer is obtained, with a diameter of 10±1.5 mm and a thickness of 0.3±0.05 mm.
[0070] The sintering aid used in Examples 1 to 12 is Li2O-BaO-SrO-CaO-B2O3-SiO2; the sintering aid used in Examples 13 to 20 is Na2O-BaO-ZnO-B2O3-CaO-Al2O3-SiO2-Cu2O; and the sintering aid used in Examples 21 to 47 is MnO-MgO-Al2O3-SiO2.
[0071] The (copper-containing) electrode layer composition used in Examples 1 to 29 includes: 52.0 wt% copper powder (i.e., the conductive metal types in Table 1-1, D...). 50 The ceramic powder (BaTi4O9, with a particle size of 0.5 μm to 1 μm) and 3.0 wt% of its D content is 0.5 μm to 1 μm. 50 The electrode layer composition used in Examples 30 to 49 comprises 1.5 ± 0.25 wt% ethyl cellulose resin (0.1 μm to 0.2 μm) and 43.5 ± 3 wt% terpineol solvent. The nickel-containing electrode layer composition includes: 47.0 wt% nickel powder (i.e., the conductive metals listed in Table 1-1, D...). 50The composition consists of 3.0 wt% ceramic powder (CaZrO3 with a D50 of 0.02 μm to 0.1 μm), 2 ± 0.25 wt% ethyl cellulose resin, and 48 ± 3 wt% terpineol solvent.
[0072] The desizing step includes heating to 300°C to 550°C using a slow heating rate (0.5°C / min to 1°C / min), holding at this temperature for a specific time, and then cooling to 40°C. The total time for the desizing step is approximately 24 to 36 hours (including the overall heating, high-temperature holding, and cooling). Additionally, in a sintering atmosphere (oxygen content of 1 ppm to 100 ppm), the sintering temperature for this step is 900°C to 1250°C, and the temperature is held for 1 to 3 hours. Specific parameters used in manufacturing Examples 1 to 49 are recorded in Tables 1-2.
[0073] Reference Example 1 (R1): Simulated sample of ceramic electrode layer
[0074] 96 parts by weight of barium titanate (BaTiO3, D) 50 A mixture of 0.5 parts by weight of MgO, 0.5 parts by weight of BaCO3, 1 part by weight of SiO2, 0.5 parts by weight of Dy2O3, 0.5 parts by weight of Y2O3, 0.5 parts by weight of MnCO3, and 0.5 parts by weight of V2O5 (with a particle size of 400±50 nm) is added to an organic solvent (a mixed solution of toluene and ethanol in a weight ratio of 1:1). Then, 3.5±0.5 parts by weight of a dispersant (manufacturer: BYK, model: DISPERBYK-2001) is added to the organic solvent to form a first mixture. Subsequently, the first mixture is ground and dispersed, and then 12±1.5 parts by weight of a binder (polyvinyl butyral resin) and 2±0.5 parts by weight of a plasticizer (DEHP) are added and thoroughly stirred to form a ceramic slurry. Next, the ceramic slurry is coated to form multiple ceramic strips with a thickness of 30 μm. Next, approximately 10 ceramic strips were stacked to form a cylindrical ingot blank and subjected to a pressure equalization step. Then, the aforementioned nickel-containing electrode layer composition was coated onto the opposing upper and lower surfaces of the cylindrical ingot blank, followed by a desizing step and a sintering step. Finally, a simulated sample of a cylindrical ceramic electrode layer was obtained, with a diameter of 10 ± 1.5 mm and a thickness of 0.3 ± 0.05 mm. The desizing and sintering steps performed in Reference Example 1 were similar to the sintering steps performed in Example 25, the only difference being the sintering temperature.
[0075] Analysis 1: Electrical analysis of the simulated sample of the ceramic electrode layer
[0076] A capacitance meter (manufacturer: Agilent Technologies Inc., model: 4278A) was used to measure the capacitance of the simulated samples of ceramic electrode layers of Reference Example 1 and Examples 1 to 49 under a 1MHz AC signal and an applied bias voltage of 1Vrms, and to calculate the dielectric constant (εr) of the ceramic material contained therein. Under the same conditions, the electrical loss factor (tanδ) of the ceramic material contained therein was also measured, and the signal transmission loss (α) was calculated by the signal propagation loss formula (Equation (1)). Furthermore, in this analysis, the ceramic electrode layers of Examples 1 to 49 were normalized with the signal transmission loss of Reference Example 1 to obtain their relative signal transmission loss (αR).
[0077] Equation (1): α = kf(εr)¹ / ²tanδ; where the dielectric constant (k) is the capacitance value of the sample measured at 25℃, and f is the frequency. Since k is related to the size of the test sample and the test temperature, and all the simulated samples of ceramic electrode layers in this analysis have the same size and test temperature, in order to facilitate the calculation and comparison of the differences in the properties of different ceramic materials, k is first fixed to 1, and then normalized by the signal transmission loss of Reference Example 1. In addition, the value of f for the simulated samples of ceramic electrode layers in Reference Example 1 and Examples 1 to 49 is 1*10⁶.
[0078] Table 1-1
[0079]
[0080]
[0081]
[0082] Table 1-2
[0083]
[0084] Examples 50 to 54 (E50 to E54): Multilayer Connector Electronic Components
[0085] First, in Example 50, 90 parts by weight of MgCaSi2O6 and 10 parts by weight of Li2O-BaO-SrO-CaO-B2O3-SiO2 were mixed in an organic solvent (a mixed solution of toluene and ethanol in a weight ratio of 1:1). Then, 3.5 ± 0.5 parts by weight of a dispersant (manufacturer: BYK, model: DISPERBYK-2001) was added to the organic solvent to form a first mixture. After grinding and dispersing the first mixture, 12 ± 1.5 parts by weight of a binder (polyvinyl butyral resin) and 2 ± 0.5 parts by weight of a plasticizer (DEHP) were added and thoroughly stirred to form a ceramic slurry. Next, the ceramic slurry was coated to form multiple identical ceramic strips with a specific thickness (approximately 8 μm) (i.e., which, after subsequent sintering, can form a ceramic top layer, a ceramic sublayer, and a ceramic bottom layer). Next, an electrode layer composition is applied to the upper surface of a portion (N sheets, N=8) of ceramic strips using a screen printing method. The remaining ceramic strips without the electrode layer composition are referred to as blank ceramic strips. Then, in a stacking apparatus, some blank ceramic strips are placed at the bottom (to form a ceramic lower cover layer); next, N ceramic strips with the electrode layer composition coated are stacked sequentially (all electrode layer compositions are facing upwards); finally, some blank ceramic strips are placed at the top (to form a ceramic upper cover layer) to form a stacked structure. The stacked structure is then subjected to a pressing and cutting step to form a green body. The green body is then subjected to a desizing step and a sintering step to obtain a sintered ceramic body. Then, electrode paste is applied to the opposite two ends of the sintered ceramic body, and a curing step is performed under a protective atmosphere to obtain the multilayer connector electronic component of Example 50. The dimensions of the multilayer connector electronic component are as follows: length 0.4±0.02mm × width 0.2±0.02mm × thickness 0.20±0.02mm. The end electrode obtained after the curing step not only has a dense structure to prevent moisture intrusion, but also allows for better bonding with the metal conductive layer within the ceramic body. Furthermore, in some embodiments, the thickness of the multilayer connector electronic component can be achieved primarily by adjusting the thickness of the upper and / or lower ceramic cover layers (e.g., the number of blank ceramic strip layers); in some embodiments, the thickness of the multilayer connector electronic component can also be achieved by adjusting the thickness of the metal conductive layer.
[0086] The desmearing step includes heating to 420±10°C using a slow heating rate (0.5°C / min to 1°C / min), holding at this temperature for 4 hours, and then cooling to 40°C; the total time for the desmearing step is approximately 48 hours (including overall heating, holding at high temperature, and cooling). Additionally, in a sintering atmosphere (oxygen content of 1ppm to 100ppm), the sintering temperature for this step is 960±30°C, and the temperature is held for 2 hours. The sintering step includes heating to 780±20°C using a slow heating rate (15°C / min to 30°C / min), holding at this temperature for 15 minutes, and then cooling to room temperature; the total time for this sintering step is approximately 1.5 hours (including overall heating, holding at high temperature, and cooling).
[0087] The electrode layer composition comprises: 52.0 wt% copper powder (D 50 The ceramic powder (BaTi4O9, with a particle size of 0.5 μm to 1 μm) and 3.0 wt% of its D content is 0.5 μm to 1 μm. 50 It contains 0.1 μm to 0.2 μm of ethyl cellulose resin, 1.5 ± 0.25 wt% of ethyl cellulose resin, and 43.5 ± 3 wt% of terpineol solvent.
[0088] The terminal electrode paste comprises 81±3 wt% copper conductive particles, 10±0.5 wt% sintering aid (B2O3-BaO-ZnO glass), 5±0.25 wt% acrylic resin, and 4±0.25 wt% terpineol solvent; wherein the copper conductive particles comprise copper conductive particles a(D 50 (0.5μm to 1μm) and copper conductive particles b (D 50 The thickness ranges from 2.0 μm to 4.0 μm, and the weight ratio is 20:80.
[0089] To ensure the experimental significance of subsequent characteristic analysis, the multilayer connector electronic components of Examples 50 to 54 were formed using the same method. The main difference between the multilayer connector electronic components of Examples 50 to 54 lies in changing the thickness of each ceramic sublayer, the thickness of each metal conductive layer, and the total number of metal conductive layers (i.e., a positive integer N), as shown in Table 2. Furthermore, the thicknesses of the ceramic upper cover layer and ceramic lower cover layer of the multilayer connector electronic components of Examples 50 to 54 were adjusted accordingly based on the target thickness and the thickness and number of the aforementioned ceramic sublayers and metal conductive layers.
[0090] Please refer to Figures 1A to 1CAs shown, the multilayer connector electronic component 1 of embodiments 50 to 54 includes: a ceramic body 10 and two-terminal electrodes 20. The ceramic body 10 has a first end face 101 and a second end face 102 facing each other; the two-terminal electrodes 20 respectively cover the first end face 101 and the second end face 102. The ceramic body 10 is formed by sequentially stacking a ceramic upper cover layer 11, a ceramic electrode layer 12, and a ceramic lower cover layer 13 from top to bottom. The ceramic electrode layer 12 includes a plurality of ceramic sublayers 121 and a connecting electrode stack group 122 (i.e., a first connecting electrode stack group); the connecting electrode stack group 122 includes a plurality of metal conductive layers 1221. In other words, the ceramic electrode layer 12 is formed by alternately stacking the ceramic sublayers 121 and the metal conductive layers 1221, and the ceramic electrode layer 12 is sandwiched between the ceramic upper cover layer 11 and the ceramic lower cover layer 13. Furthermore, the metal conductive layers 1221 are all electrically connected to the two-terminal electrodes 20. Furthermore, although the number of metal conductive layers shown in Figure 1 is 14, the number of ceramic sub-layers 121 and metal conductive layers 1221 in the figure is mainly for illustrative purposes and is not limited to a large number. The actual number of layers in each embodiment is described in Table 2. In some other embodiments, each end electrode 20 may sequentially include a first sub-end electrode 21 and a second sub-end electrode 22 from the inside out, and the second sub-end electrode 22 is also covered with a flux layer 30.
[0091] Furthermore, the length of each metal conductive layer 1221 is the same as the length of the ceramic body, which is the parallel distance between the first end face 101 and the second end face 102. In this way, each metal conductive layer 1221 can be connected to the two-terminal electrode 20.
[0092] Table 2
[0093]
[0094] Examples 55 to 63 (E55 to E63): Multilayer Connector Electronic Components
[0095] The methods used in preparing Examples 55 to 59 are similar to those used in preparing the multilayer connector electronic components of Example 50. The main differences are: the main powder material used in Example 50 is changed from 90 parts by weight of MgCaSi2O6 to 90 parts by weight of BaTi4O9; the glass material is changed from 10 parts by weight of Li2O-BaO-SrO-CaO-B2O3-SiO2 to 10 parts by weight of Na2O-BaO-ZnO-B2O3-CaO-Al2O3-SiO2-Cu2O; and the sintering temperature is changed from 960±30℃ to 950±30℃. Furthermore, the thickness of each ceramic sublayer, the thickness of each metal conductive layer, and the total number of metal conductive layers (i.e., positive integer N) of the multilayer connector electronic components of Examples 55 to 59 are shown in Table 3. In addition, the thickness of the ceramic upper cover layer and the ceramic lower cover layer of the multilayer connector electronic components of Examples 55 to 59 are adjusted according to the target thickness and the thickness and number of the ceramic sublayers and metal conductive layers.
[0096] The methods used in preparing Examples 60 to 63 are similar to those used in preparing the multilayer connector electronic component of Example 55, with the main difference being that the main powder material used in Example 55 is changed from 90 parts by weight of BaTi4O9 to 90 parts by weight of Ba2Ti9O. 20 The glass material was changed from 10 parts by weight of Na2O-BaO-ZnO-B2O3-CaO-Al2O3-SiO2-Cu2O to 10 parts by weight of Na2O-BaO-ZnO-B2O3-CaO-Al2O3-SiO2-Cu2O. Furthermore, the thickness of each ceramic sublayer, the thickness of each metal conductive layer, and the total number of metal conductive layers (i.e., a positive integer N) of the multilayer connector electronic components in Examples 60 to 63 are shown in Table 3. In addition, the thickness of the ceramic upper cover layer and the ceramic lower cover layer of the multilayer connector electronic components in Examples 60 to 63 are adjusted accordingly based on the target thickness and the thickness and number of the aforementioned ceramic sublayers and metal conductive layers.
[0097] Table 3
[0098]
[0099] Examples 64 to 67 (E64 to E67): Multilayer Connector Electronic Components
[0100] The method used in preparing Example 64 is similar to the method used in preparing the multilayer connector electronic component in Example 52. The main difference is that the main powder material used in Example 52 is changed from 90 parts by weight of MgCaSi2O6 to 90 parts by weight of MgSiO4.
[0101] The method used in preparing Example 65 is similar to the method used in preparing the multilayer connector electronic component in Example 52. The main difference is that the main powder material used in Example 52 is changed from 90 parts by weight of MgCaSi2O6 to 90 parts by weight of Zn2SiO4.
[0102] The method used in preparing Example 66 is similar to the method used in preparing the multilayer connector electronic component in Example 52. The main difference is that the main powder material used in Example 52 is changed from 90 parts by weight of MgCaSi2O6 to 90 parts by weight of CaZrO3, the glass material is changed from 10 parts by weight of Li2O-BaO-SrO-CaO-B2O3-SiO2 to 10 parts by weight of MnO-MgO-Al2O3-SiO2, and the sintering temperature is changed from 960±30℃ to 970±30℃.
[0103] The method used in preparing Example 67 is similar to the method used in preparing the multilayer connector electronic component in Example 52, the main difference being that the main powder material used in Example 52 is changed from 90 parts by weight of MgCaSi2O6 to 90 parts by weight of (Ca 0.7 Sr 0.3 (Zr) 0.96 Ti 0.04 The glass material was changed from 10 parts by weight of Li2O-BaO-SrO-CaO-B2O3-SiO2 to 10 parts by weight of MnO-MgO-Al2O3-SiO2, and the sintering temperature was changed from 960±30℃ to 975±30℃.
[0104] Furthermore, the thickness of each ceramic sublayer and the thickness of each metal conductive layer of the multilayer connector electronic components in Examples 64 to 67 are shown in Table 4; the total number of metal conductive layers (N) of the multilayer connector electronic components in Examples 64 to 67 is 16. In addition, the thickness of each ceramic top cover layer and ceramic bottom cover layer of each multilayer connector electronic component in Examples 64 to 67 is adjusted according to the target thickness and the thickness and number of the aforementioned ceramic sublayers and metal conductive layers.
[0105] Table 4
[0106]
[0107] Examples 68 to 75 (E68 to E75): Multilayer Connector Electronic Components
[0108] The methods used in preparing Examples 68 to 72 are similar to those used in preparing the multilayer connector electronic component of Example 50, with the main difference being that the main powder material used in Example 50 is changed from 90 parts by weight of MgCaSi2O6 to 97 parts by weight of (Ca 0.7 Sr 0.3(Zr) 0.96 Ti 0.04 The 10 parts by weight of Li2O-BaO-SrO-CaO-B2O3-SiO2 were replaced with 3 parts by weight of MnO-MgO-Al2O3-SiO2; furthermore, the desizing temperature was changed to 320±10℃, the desizing holding time was changed to 2 hours, the sintering temperature was changed to 1250±30℃, and the types of base metal powder and ceramic powder in the electrode layer composition were different; furthermore, the thickness of each ceramic sublayer, the thickness of each metal conductive layer, and the total number of metal conductive layers (i.e., positive integer N) of the multilayer connector electronic components of Examples 68 to 72 are shown in Table 5. In addition, the thickness of each ceramic upper cover layer and ceramic lower cover layer of the multilayer connector electronic components of Examples 68 to 72 were adjusted according to the target thickness and the thickness and number of the above-mentioned ceramic sublayers and metal conductive layers.
[0109] The electrode layer composition used in Examples 68 to 72 comprises: 47.0 wt% nickel powder (D50 of 0.1 μm to 0.5 μm), 3.0 wt% ceramic powder (CaZrO3, whose D50 is 0.1 μm to 0.5 μm), and 3.0 wt% ceramic powder (CaZrO3, whose D50 is 0.1 μm to 0.5 μm). 50 It consists of 0.02 μm to 0.1 μm, 2 ± 0.25 wt% ethyl cellulose resin, and 48 ± 3 wt% terpineol solvent.
[0110] The method used in preparing Example 73 is similar to the method used in preparing the multilayer connector electronic component of Example 68, the main difference being that: the main powder material used in Example 68 is changed from 97 parts by weight of (Ca) 0.7 Sr 0.3 (Zr) 0.96 Ti 0.04 O3 was changed to 98 parts by weight of (Ca) 0.68 Sr 0.32 (Zr) 0.9 Ti 0.1 )O3, 3 parts by weight of MnO-MgO-Al2O3-SiO2 were changed to 2 parts by weight of MnO-MgO-Al2O3-SiO2.
[0111] The method used in preparing Example 74 is similar to the method used in preparing the multilayer connector electronic component in Example 73, the main difference being that: the main powder material used in Example 73 is changed from 98 parts by weight of (Ca) 0.68 Sr 0.32 (Zr) 0.9 Ti 0.1 O3 was changed to 98 parts by weight of (Ca) 0.68 Sr 0.32 (Zr) 0.66 Ti 0.34 )O3.
[0112] The method used in preparing Example 75 is similar to the method used in preparing the multilayer connector electronic component in Example 73, the main difference being that: the main powder material used in Example 73 is changed from 98 parts by weight of (Ca) 0.68 Sr 0.32 (Zr) 0.9 Ti 0.1 O3 was changed to 98 parts by weight of (Sr) 0.14 Ca 0.82 Ba 0.04 (Zr) 0.46 Ti 0.54 )O3.
[0113] The thickness of each ceramic sublayer and each metal conductive layer of the multilayer connector electronic components in Examples 73 to 75 are shown in Table 5; the total number of metal conductive layers (N) of the multilayer connector electronic components in Examples 73 to 75 is 16. Furthermore, the thickness of the ceramic top cover layer and ceramic bottom cover layer of each multilayer connector electronic component in each embodiment is adjusted according to the target thickness and the thickness and number of the aforementioned ceramic sublayers and metal conductive layers.
[0114] Table 5
[0115]
[0116] Examples 57-I to 57-II (E57-I to E57-II): Multilayer Connector Electronic Components
[0117] The methods used to prepare Examples 57-I to 57-II are similar to those used to prepare the multilayer connector electronic component of Example 57, with the main difference being the change in the type and ratio of copper conductive particles in the terminal electrode paste, as detailed in Table 6. However, the terminal electrode pastes used in Examples 57-I to 57-II and Example 57 all contain the same amount of copper conductive particles, B2O3-BaO-ZnO glass, acrylic resin, and terpineol solvent.
[0118] Table 6
[0119]
[0120] Examples 57-III to 57-IX (E57-III to E57-IX): Multilayer Connector Electronic Components
[0121] The methods used to prepare Examples 57-III to 57-IX are similar to those used to prepare the multilayer connector electronic component of Example 57. The electrode layer compositions used in Examples 57-III to 57-IX and Example 57 all contain the same amount of ethyl cellulose resin and terpineol solvent. The main difference lies in the change of copper powder (D...) in the electrode layer composition.50 (0.5μm to 1μm) and BaTi4O9 (D 50 The proportions (from 0.1μm to 0.2μm) and sintering temperatures are detailed in Table 7.
[0122] Table 7
[0123]
[0124] Examples 70-I to 70-VII (E70-I to E70-VII): Multilayer Connector Electronic Components
[0125] The methods used in preparing Examples 70-I to 70-VII are similar to those used in preparing the multilayer connector electronic component of Example 70. The electrode layer compositions used in Examples 70-I to 70-VII and Example 70 all contain the same amount of ethyl cellulose resin and terpineol solvent. The main difference lies in the change of nickel powder (D) in the electrode layer composition. 50 (0.1 μm to 0.5 μm) and CaZrO3 (D 50 The proportions (from 0.02μm to 0.1μm) and sintering temperatures are detailed in Table 8.
[0126] Table 8
[0127]
[0128]
[0129] Reference Example 2 (R2): Thick-film connector electronic components
[0130] Please refer to Figure 9 As shown, Example 2 was prepared using existing technology, with the following specific steps: First, an alumina substrate S was prepared, and two-terminal electrodes C1 (manufacturer: Shoei, model: D-44437) with a thickness of approximately 20 μm were printed on the upper surface of the alumina substrate S near the left and right ends, respectively. Next, two-terminal electrodes C3 (manufacturer: Namics, model: SR4382) with a thickness of approximately 20 μm were printed on the lower surface of the alumina substrate S near the left and right ends, respectively. Next, the alumina substrate S with printed terminal electrodes C1 and C3 underwent a first sintering step by slowly increasing the temperature; wherein the first sintering temperature was 850°C, the holding time was 15 minutes, and the total time for completing the first sintering step (heating, holding, and cooling) was 90 minutes.
[0131] Next, connecting electrodes R (made of silver, manufacturer: SMM, model: R-01U-F) with a thickness of approximately 15 μm are printed on the surface of the alumina substrate S, and the connecting electrodes R are connected to the two end electrodes C1 respectively. Subsequently, a second sintering step is performed by slowly increasing the temperature; wherein the second sintering temperature is 850°C, the holding time is 15 minutes, and the complete time for the second sintering step (heating, holding, and cooling) is 90 minutes. Afterwards, a protective layer G1 is covered on the connecting electrodes R and sintered at 600°C; after laser cutting to adjust the resistance value, a protective layer G2 is covered on the protective layer G1, and the protective layer G2 is an insulating material. After a strip-folding step, end electrodes C2 (silver electrodes) are formed on the left and right end faces of the alumina substrate S by sputtering. Then, after a pellet-folding step, a first protective electrode P1 (nickel) and a second protective electrode P2 (tin) are sequentially formed on the outer surfaces of the end electrodes C1 to C3 by electroplating. The finished product dimensions of Reference Example 2 are as follows: length 0.4±0.02mm × width 0.2±0.02mm × thickness 0.13±0.02mm.
[0132] Reference Example 3 (R3): Multilayer Connector Electronic Components
[0133] The method used to prepare Reference Example 3 is similar to the method used to prepare the multilayer connector electronic component of Example 73, the main difference being that the main powder material used in Example 73 is changed to 96 parts by weight of BaTiO3 (D 50 The composite material contains 0.5 parts by weight of MgO (particle size 400±50 nm), 0.5 parts by weight of BaCO3, 1 part by weight of SiO2, 0.5 parts by weight of Dy2O3, 0.5 parts by weight of Y2O3, 0.5 parts by weight of MnCO3, and 0.5 parts by weight of V2O5, without adding MnO-MgO-Al2O3-SiO2; and the sintering temperature is changed from 1250±30℃ to 1200±30℃. The thickness of each ceramic sublayer, the thickness of each metal conductive layer, and the total number of metal conductive layers (N) of the multilayer connector electronic component in Reference Example 3 are the same as in Example 73.
[0134] Analysis 2: Resistance Value and Resistance Tolerance Analysis
[0135] First, the DC resistance values (hereinafter referred to as "resistance") of Reference Examples 2, 3, and Examples 50 to 75, 57-I to 57-IX, and 70-I to 70-VII were measured according to JIS C 5201-1:Clause 4.5 using a four-wire resistance measurement system (manufacturer: Bankala Technology, model: RM3543). Furthermore, the resistance tolerance for each group was calculated according to Equation (2): Resistance tolerance (COV%) = Resistance standard deviation / Resistance average value. The experimental results for Reference Examples 2 and Examples 50 to 67 are recorded in Table 9-1, the experimental results for Examples 57 and 57-I to 57-IX are recorded in Table 9-2, the experimental results for Examples 68 to 75 are recorded in Table 9-3, and the experimental results for Examples 70 and 70-I to 70-VII are recorded in Table 9-4. The resistance values recorded for each of the aforementioned groups are the average values of the 24 connector electronic components measured.
[0136] If the measured resistance value of the connector electronic component is less than 50mΩ, it indicates that the component impedance is low and is judged as "good"; conversely, if the measured resistance value of the connector electronic component is equal to or greater than 50mΩ, it indicates that the component impedance is high and is judged as "unqualified".
[0137] If the resistance tolerance of the connector electronic component is less than or equal to 3%, its electrical stability is considered good; conversely, if the measured resistance tolerance of the connector electronic component is greater than 3%, its electrical stability is considered poor.
[0138] Analysis 3: Bending Failure Rate Analysis
[0139] According to JIS C 5201-1:Clause 4.33, firstly, the thick-film connector electronic components of Reference Example 2 and the multilayer connector electronic components of Reference Example 3 and various embodiments were mounted on a 90mm standard grade FR-4 copper-clad laminate to prepare the test samples. Next, the test samples were pressed down using a universal testing machine (manufacturer: Qualitest, model: QM-2001F), and their appearance and metallographic cross-section were observed using a metallographic microscope (manufacturer: OLYMPUS, model: BX60M) to check for breakage. The breakage rate was evaluated based on the cross-section (i.e., 100%). The relevant parameters for this analysis are as follows: indenter curvature radius R5, pressing rate 1.0mm / s, bending displacement of the test sample 3mm, and duration 10±1 seconds.
[0140] Specifically, if the fracture rate of the cross section is 0%, its bending toughness is rated as "Excellent"; if the fracture rate of the cross section is greater than 0% and less than or equal to 20%, its bending toughness is rated as "Good"; if the fracture rate of the cross section is greater than 20% and less than or equal to 50%, its bending toughness is rated as "Fair"; if the fracture rate of the cross section is greater than 50% and less than or equal to 80%, its bending toughness is rated as "Acceptable"; and if the fracture rate of the cross section is greater than 80%, its bending toughness is rated as "Inferior".
[0141] Analysis 4: Short-duration instantaneous load failure rate
[0142] First, the thick-film connector electronic components of Reference Example 2 and the multilayer connector electronic components of Reference Example 3 and other embodiments were soldered onto a test board. According to the JIS C 5201-1:Clause 4.13 test specification, a current (1.25 amps) was applied to each group of test samples in a chip resistance STOL test system using a power supply (manufacturer: Keysight Technologies Co., Ltd., model: E3640A) that was cycled on and off (5 seconds on, 5 seconds off). The resistance was observed to see if the components were open-circuited due to the high current melting or if the resistance rose above 50 mΩ. If any of these conditions were present, the sample was considered "failed." Each group measured 24 identical connector electronic components, and the failure rate was calculated as the percentage of failures out of the total. For example, in embodiment E57-VI, there were 2 failures, so the failure rate was 2 / 24 = 8%.
[0143] Specifically, if the obtained short-term instantaneous load failure rate is 0%, its reliability is rated as "good"; if the obtained short-term instantaneous load failure rate is greater than 0% and less than or equal to 15%, its reliability is rated as "fair"; and if the obtained short-term instantaneous load failure rate is greater than 15%, its reliability is rated as "poor".
[0144] Analysis 5: Water vapor intrusion failure test
[0145] According to JIS C 5201-1:Clause 4.24, firstly, the thick-film connector electronic components of Reference Example 2 and the multilayer connector electronic components of Reference Example 3 and various embodiments were placed in a constant temperature and humidity chamber (manufacturer: Hitachi, model: EC-86MHHPE) for 1000 hours; wherein the temperature of the constant temperature and humidity chamber was 40±2℃ and the relative humidity was 90% to 95%, and a current (0.5 amps) was applied to each sample to be tested. Next, a power supply (manufacturer: Keysight Technologies Co., Ltd., model: E3640A) applied a current of 0.5 amps to each group of samples to be tested in a switching cycle (on for 1.5 hours, off for 0.5 hours), and observed whether any components were open-circuited or whether their resistance rose to greater than 50mΩ. If the aforementioned conditions were present, it was determined as "failure"; wherein, 24 identical connector electronic components were measured in each group, and the "percentage of failures out of the total" was used as its failure rate.
[0146] If the obtained water vapor intrusion failure rate is 0%, its reliability is rated as "good"; if the obtained water vapor intrusion failure rate is greater than 0% and less than or equal to 30%, its reliability is rated as "fair"; if the obtained short-term instantaneous load failure rate is greater than 30%, its reliability is rated as "poor".
[0147] Table 9-1
[0148]
[0149]
[0150] Table 9-2
[0151]
[0152]
[0153] Table 9-3
[0154]
[0155] Table 9-4
[0156]
[0157]
[0158] Analysis 6: Mechanical Characteristics Analysis
[0159] In accordance with JIS R1607 and JIS R1610 standards, standard indentation fracture technique was employed. This analysis was conducted on Examples 52, 57, 62, 64 to 68, 73 to 75, and Reference Example 3 (each containing 20 multilayer connector electronic components) using a nanoindenter system (manufacturer: Keysight Technologies, model: Nano Indenter G200). A nanoindentation was applied to the upper and lower ceramic capping layers of each specimen, and the average Young's modulus (E) and average hardness (H) of the specimen were calculated from the load-depth curves obtained during the indentation process. The relevant parameters are as follows: indenter displacement resolution < 0.01 nm, maximum indentation depth 500 μm, and maximum indentation load 500 mN. The experimental results are recorded in Table 10.
[0160] If the obtained average Young's coefficient is above 130 GPa, its mechanical properties are rated as "good"; if the obtained average Young's coefficient is greater than 90 GPa and less than 130 GPa, its mechanical properties are rated as "fair"; if the obtained average Young's coefficient is less than or equal to 90 GPa, its mechanical properties are rated as "poor".
[0161] Specifically, if the obtained average hardness is between 7.9 GPa and 13 GPa, its mechanical properties are rated as "good"; if the obtained average hardness is greater than or equal to 6.7 GPa and less than 7.9 GPa, its mechanical properties are rated as "fair"; and if the obtained average hardness is less than 6.7 GPa, its mechanical properties are rated as "poor".
[0162] Furthermore, according to the Lawn-Evans-Marshall (LEM) model, the bending strength of a material is positively correlated with (E / H)1 / 2. Therefore, the (E / H)1 / 2 value is further calculated by taking the average Young's coefficient and average hardness mentioned above. If the obtained (E / H)1 / 2 value is 4 or above, its reliability is rated as "good"; if the obtained (E / H)1 / 2 value is less than 4, its reliability is rated as "poor".
[0163] Analysis 7: Insulation resistance IR
[0164] The following analysis was performed on Examples 52, 57, 62, 64 to 68, 73 to 75 and Reference Example 3 using a high resistance meter (manufacturer: Keysight Technology Co., Ltd., model: Keysight 4339B): a voltage (50V) was applied to each test piece and its leakage current was measured. The insulation resistance was obtained by dividing the voltage by the leakage current and the results are recorded in Table 10.
[0165] If the insulation resistance is greater than 5*109Ω, it indicates that the component can avoid leakage current when in contact with the outside, and the current carrying capacity is rated as "good".
[0166] Table 10
[0167]
[0168] Example 76: Multilayer Connector Electronic Components
[0169] Please refer to Figures 2A to 2C As shown, this embodiment uses a similar fabrication method to the multilayer connector electronic component 1 of embodiment 56 to produce the multilayer connector electronic component 1 of this embodiment. The main difference is that the multilayer connector electronic component 1 of embodiment 56 has one set of connecting electrode multilayer groups 122, while the multilayer connector electronic component 1 of this embodiment has two sets of connecting electrode multilayer groups 122 (i.e., the first connecting electrode multilayer group and the second connecting electrode multilayer group). The dimensions of the multilayer connector electronic component 1 of this embodiment are as follows: length 0.4±0.02mm × width 0.2±0.02mm × thickness 0.13±0.02mm.
[0170] Specifically, in this embodiment, the total number of metal conductive layers 1221 in the multilayer connector electronic component 1 is still 14. However, in the fabrication process of this embodiment, an additional blank ceramic strip is sandwiched between the ceramic strip forming the 7th ceramic sublayer 121 and the ceramic strip forming the 8th ceramic sublayer 121, making the vertical spacing between the 7th and 8th metal conductive layers (from top to bottom) larger than the vertical spacing between other metal conductive layers. Therefore, the 14 metal conductive layers 1221 can be divided into two groups of interconnecting electrode stacked layers 122. That is, as... Figure 2C As shown, viewed from the first end face 101 to the second end face 102 of the ceramic body 10, the upper (first) connecting electrode stack 122 and the lower (second) connecting electrode stack 122 are arranged side by side in the vertical direction of the ceramic body 10. The stacked connector electronic component 1 further achieves the target thickness by adjusting the thickness of the upper ceramic cover layer 11 and / or the lower ceramic cover layer 13.
[0171] Furthermore, this embodiment is analyzed using the analyses 2 to 5 described above, and the experimental results are recorded in Table 11.
[0172] Example 77: Multilayer Connector Electronic Components
[0173] Please refer to Figures 3A to 3C As shown, this embodiment uses a similar fabrication method to the multilayer connector electronic component 1 of embodiment 56 to produce the multilayer connector electronic component 1 of this embodiment. The main difference is that the multilayer connector electronic component 1 of embodiment 56 has one set of interconnecting electrode stacks 122, while the multilayer connector electronic component 1 of this embodiment has two sets of interconnecting electrode stacks 122 (i.e., the first interconnecting electrode stack and the second interconnecting electrode stack). The dimensions of the multilayer connector electronic component 1 of this embodiment are as follows: length 0.4±0.02mm × width 0.2±0.02mm × thickness 0.13±0.02mm.
[0174] Specifically, in this embodiment, the multilayer connector electronic component 1 is printed by adjusting the printed pattern, so that each metal conductive layer 1221 of embodiment 56 is printed as two parallel metal conductive layers 1221 spaced apart by a horizontal distance H1 in the horizontal direction of the ceramic body 10. Therefore, the 14 layers of metal conductive layers 1221 (counted from top to bottom) can be divided into two groups of interconnecting electrode multilayer groups 122. That is, as Figure 3C As shown, when viewed from the first end face 101 to the second end face 102 of the ceramic body 10, the front (first) connecting electrode stack 122 and the rear (second) connecting electrode stack 122 are arranged side by side in the horizontal direction of the ceramic body 10.
[0175] Furthermore, this embodiment is analyzed using the analyses 2 to 5 described above, and the experimental results are recorded in Table 11.
[0176] Example 78: Multilayer Connector Electronic Components
[0177] Please refer to Figures 4A to 4C As shown, this embodiment uses a similar fabrication method to the multilayer connector electronic component 1 of embodiment 76 to produce the multilayer connector electronic component 1 of this embodiment. The main difference is that the multilayer connector electronic component 1 of embodiment 76 has two sets of interconnecting electrode stacks 122, while the multilayer connector electronic component 1 of this embodiment has four sets of interconnecting electrode stacks 122 (i.e., the first to the fourth interconnecting electrode stacks). The dimensions of the multilayer connector electronic component 1 of this embodiment are as follows: length 0.4±0.02mm × width 0.2±0.02mm × thickness 0.13±0.02mm.
[0178] Specifically, in this embodiment, the multilayer connector electronic component 1 is printed as two parallel metal conductive layers 1221 with a horizontal spacing H1 between them in the horizontal direction of the ceramic body 10 by adjusting the printed pattern. Therefore, the original single metal conductive layer 1221 can be divided into two metal conductive layers 1221. That is, as... Figure 4C As shown, viewed from the first end face 101 to the second end face 102 of the ceramic body 10, the upper (first) connecting electrode stack 122 and the lower (third) connecting electrode stack 122 are arranged side by side in the vertical direction of the ceramic body 10; the front (first) connecting electrode stack 122 and the rear (second) connecting electrode stack 122 are arranged side by side in the horizontal direction of the ceramic body 10; the front (third) connecting electrode stack 122 and the rear (fourth) connecting electrode stack 122 are arranged side by side in the horizontal direction of the ceramic body 10.
[0179] Furthermore, this embodiment is analyzed using the analyses 2 to 5 described above, and the experimental results are recorded in Table 11.
[0180] Example 79: Multilayer Connector Electronic Components
[0181] Please refer to Figures 5A to 5C As shown, this embodiment uses a similar fabrication method to the multilayer connector electronic component 1 of embodiment 76 to produce the multilayer connector electronic component 1 of this embodiment. The main difference is that the multilayer connector electronic component 1 of embodiment 76 has two sets of interconnecting electrode stacks 122, while the multilayer connector electronic component 1 of this embodiment has six sets of interconnecting electrode stacks 122 (i.e., the first to the sixth interconnecting electrode stacks). The dimensions of the multilayer connector electronic component 1 of this embodiment are as follows: length 0.4±0.02mm × width 0.2±0.02mm × thickness 0.13±0.02mm.
[0182] Specifically, in this embodiment, the multilayer connector electronic component 1 is printed by adjusting the printed pattern, so that each metal conductive layer 1221 of embodiment 76 is printed as a three-metal conductive layer 1221 that are parallel to each other and spaced apart by a horizontal distance H1 in the horizontal direction of the ceramic body 10. Therefore, the original single metal conductive layer 1221 can be divided into three metal conductive layers 1221. That is to say, as Figure 5CAs shown, viewed from the first end face 101 to the second end face 102 of the ceramic body 10, the upper (first) connecting electrode stack 122 and the lower (fourth) connecting electrode stack 122 are arranged side by side in the vertical direction of the ceramic body 10; the upper (second) connecting electrode stack 122 and the lower (fifth) connecting electrode stack 122 are arranged side by side in the vertical direction of the ceramic body 10; the upper (third) connecting electrode stack 122 and the lower (sixth) connecting electrode stack 122 are also arranged side by side in the vertical direction of the ceramic body 10. Group 122 is arranged side by side in the vertical direction of the ceramic body 10; the front (first) connecting electrode stack group 122, the middle (second) connecting electrode stack group 122 and the rear (third) connecting electrode stack group 122 are arranged side by side in the horizontal direction of the ceramic body 10; the front (fourth) connecting electrode stack group 122, the middle (fifth) connecting electrode stack group 122 and the rear (sixth) connecting electrode stack group 122 are arranged side by side in the horizontal direction of the ceramic body 10.
[0183] Furthermore, this embodiment is analyzed using the analyses 2 to 5 described above, and the experimental results are recorded in Table 11.
[0184] Example 80: Multilayer Connector Electronic Components
[0185] Please refer to Figures 6A to 6C As shown, this embodiment uses a similar fabrication method to the multilayer connector electronic component 1 of embodiment 56 to produce the multilayer connector electronic component 1 of this embodiment. The main difference is that the multilayer connector electronic component 1 of embodiment 56 has one set of connecting electrode multilayer groups 122, while the multilayer connector electronic component 1 of this embodiment has three sets of connecting electrode multilayer groups 122 (i.e., the first to the third connecting electrode multilayer groups). The dimensions of the multilayer connector electronic component 1 of this embodiment are as follows: length 0.4±0.02mm × width 0.2±0.02mm × thickness 0.13±0.02mm.
[0186] Specifically, in this embodiment, the multilayer connector electronic component 1 is printed by adjusting the printed pattern, so that each metal conductive layer 1221 of Embodiment 56 is printed as three metal conductive layers 1221 that are parallel to each other and spaced apart by a horizontal distance H1 in the horizontal direction of the ceramic body 10. Therefore, the 14 metal conductive layers 1221 (counted from top to bottom) can be divided into three groups of interconnecting electrode multilayer groups 122. That is, as Figure 6C As shown, when viewed from the first end face 101 to the second end face 102 of the ceramic body 10, the front (first) connecting electrode stack 122, the middle (second) connecting electrode stack 122 and the rear (third) connecting electrode stack 122 are arranged side by side in the horizontal direction of the ceramic body 10.
[0187] Furthermore, this embodiment is analyzed using the analyses 2 to 5 described above, and the experimental results are recorded in Table 11.
[0188] Example 81: Multilayer Connector Electronic Components
[0189] Please refer to Figures 7A to 7C As shown, this embodiment uses a similar fabrication method to the multilayer connector electronic component 1 of embodiment 80 to produce the multilayer connector electronic component 1 of this embodiment. The main difference is that the multilayer connector electronic component 1 of embodiment 80 has three sets of interconnecting electrode stacks 122, while the multilayer connector electronic component 1 of this embodiment has nine sets of interconnecting electrode stacks 122 (i.e., the first to the ninth interconnecting electrode stacks). The dimensions of the multilayer connector electronic component 1 of this embodiment are as follows: length 0.4±0.02mm × width 0.2±0.02mm × thickness 0.13±0.02mm.
[0190] Specifically, in this embodiment, the number of metal conductive layers 1221 in the multilayer connector electronic component 1 from top to bottom is still 14. However, in the manufacturing process of this embodiment, an extra blank ceramic strip is sandwiched between the ceramic strips forming the electrode layer composition of the fifth ceramic sublayer 121 and the ceramic strips forming the electrode layer composition of the sixth ceramic sublayer 121, and an extra blank ceramic strip is sandwiched between the ceramic strips forming the electrode layer composition of the ninth ceramic sublayer 121 and the ceramic strips forming the electrode layer composition of the tenth ceramic sublayer 121. This makes the vertical spacing between the fifth and sixth metal conductive layers 1221 (from top to bottom), and the vertical spacing between the ninth and tenth metal conductive layers 1221, larger than the vertical spacing between other metal conductive layers. Accordingly, the 14-layer conductive metal layer 1221 can be divided into upper, middle, and lower connecting electrode stack groups 122. That is, as... Figure 7CAs shown, viewed from the first end face 101 to the second end face 102 of the ceramic body 10, the upper (first) connecting electrode stack 122, the middle (fourth) connecting electrode stack 122, and the lower (seventh) connecting electrode stack 122 are arranged side by side in the vertical direction of the ceramic body 10; the upper (second) connecting electrode stack 122, the middle (fifth) connecting electrode stack 122, and the lower (eighth) connecting electrode stack 122 are arranged side by side in the vertical direction of the ceramic body 10; the upper (third) connecting electrode stack 122, the middle (sixth) connecting electrode stack 122, and the lower (ninth) connecting electrode stack 122 are arranged side by side in the vertical direction of the ceramic body 10. The stacked connector electronic component 1 further achieves the target thickness by adjusting the thickness of the upper ceramic cover layer 11 and / or the lower ceramic cover layer 13.
[0191] Furthermore, the multilayer connector electronic component 1 in this embodiment also achieves this through the adjustment of the printed pattern, so that the ceramic body 10 can simultaneously have three metal conductive layers 1221 at the same horizontal height, and the adjacent metal conductive layers 1221 have a horizontal spacing H1. In other words, when viewed from the first end face 101 to the second end face 102 of the ceramic body 10, the front (first) connecting electrode stack 122, the middle (second) connecting electrode stack 122 and the rear (third) connecting electrode stack 122 are arranged side by side in the horizontal direction of the ceramic body 10; the front (fourth) connecting electrode stack 122, the middle (fifth) connecting electrode stack 122 and the rear (sixth) connecting electrode stack 122 are arranged side by side in the horizontal direction of the ceramic body 10; the front (seventh) connecting electrode stack 122, the middle (eighth) connecting electrode stack 122 and the rear (ninth) connecting electrode stack 122 are arranged side by side in the horizontal direction of the ceramic body 10.
[0192] Furthermore, this embodiment is analyzed using the analyses 2 to 5 described above, and the experimental results are recorded in Table 11.
[0193] Example 82: Multilayer Connector Electronic Components
[0194] Please refer to Figures 8A to 8CAs shown, this embodiment uses a similar fabrication method to the multilayer connector electronic component 1 of embodiment 81 to produce the multilayer connector electronic component 1 of this embodiment. The main difference is that the multilayer connector electronic component 1 of embodiment 81 has nine sets of interconnecting electrode stacks 122, while the multilayer connector electronic component 1 of this embodiment has twelve sets of interconnecting electrode stacks 122 (i.e., the first to the twelfth interconnecting electrode stacks). The dimensions of the multilayer connector electronic component 1 of this embodiment are as follows: length 0.4±0.02mm × width 0.2±0.02mm × thickness 0.13±0.02mm.
[0195] Specifically, in this embodiment, the multilayer connector electronic component 1 also adjusts the printed pattern so that the ceramic body 10 can simultaneously have four metal conductive layers 1221 at the same horizontal height, and adjacent metal conductive layers 1221 have a horizontal spacing H1. That is, looking from the first end face 101 to the second end face 102 of the ceramic body 10, the front (first) connecting electrode multilayer group 122, the front middle (second) connecting electrode multilayer group 122, the rear middle (third) connecting electrode multilayer group 122, and the rear (fourth) connecting electrode multilayer group 122 are arranged side by side in the horizontal direction of the ceramic body 10; the front (fifth) connecting electrode multilayer group 122, the front middle (sixth) connecting electrode multilayer group 122, and the rear (fifth) connecting electrode multilayer group 122 are arranged side by side in the horizontal direction of the ceramic body 10. Layer group 122, the rear middle side (seventh) connecting electrode stack group 122 and the rear side (eighth) connecting electrode stack group 122 are arranged side by side in the horizontal direction of the ceramic body 10; the front side (ninth) connecting electrode stack group 122, the front middle side (tenth) connecting electrode stack group 122, the rear middle side (eleventh) connecting electrode stack group 122 and the rear side (twelfth) connecting electrode stack group 122 are arranged side by side in the horizontal direction of the ceramic body 10.
[0196] Furthermore, this embodiment is analyzed using the analyses 2 to 5 described above, and the experimental results are recorded in Table 11.
[0197] Table 11
[0198]
[0199]
[0200] Discussion of Experimental Results
[0201] Even though the electrical analysis of Examples 1 to 49 is only a simulation analysis of the ceramic electrode layer, it is clear from the experimental results in Table 1 that, since the present invention uses a specific main powder material with low dielectric constant and low dielectric loss factor, the signal transmission loss of the ceramic electrode layer of the present invention is significantly lower than that of Reference Example 1 of the prior art.
[0202] Furthermore, comparing the analytical results of Examples 1 to 4, Examples 5 to 8, and Examples 9 to 12, when the base metal of the conductive metal layer is copper, and the ceramic material comprises the silicate-based microwave dielectric material and the glass material (Li2O-BaO-SrO-CaO-B2O3-SiO2), a glass material content of 8 to 10 parts by weight can achieve a lower dielectric loss factor and lower signal transmission loss. Similarly, comparing the analytical results of Examples 13 to 16 and Examples 17 to 20, when the base metal of the conductive metal layer is copper, and the ceramic material comprises the barium titanate-based microwave dielectric material and the glass material (Na2O-BaO-ZnO-B2O3-CaO-Al2O3-SiO2-Cu2O), a glass material content of 8 to 10 parts by weight can achieve a lower dielectric loss factor and lower signal transmission loss. Similarly, comparing the analytical results from Examples 21 to 24, when the base metal of the conductive metal layer is copper, and the ceramic material comprises the calcium zirconate and the glass material (MnO-MgO-Al2O3-SiO2), a glass material content of 8 to 10 parts by weight results in a lower dielectric loss factor and lower signal transmission loss. Furthermore, comparing the analytical results from Examples 28 to 29, when the base metal of the conductive metal layer is copper, and the ceramic material comprises the strontium titanate compound and the glass material (MnO-MgO-Al2O3-SiO2), a glass material content of 10 to 12 parts by weight results in a lower dielectric loss factor and lower signal transmission loss. Furthermore, comparing the analytical results of Examples 30 to 34, Examples 35 to 39, and Examples 40 to 49, it is found that when the base metal of the conductive metal layer is nickel, and the ceramic material comprises the strontium titanate compound and the glass material (MnO-MgO-Al2O3-SiO2), the content of the glass material is 1 part by weight to 3 parts by weight, which can have a lower dielectric loss factor and lower signal transmission loss.
[0203] Furthermore, the analysis results in Tables 9-1 and 9-3 show that the multilayer connector electronic components of each embodiment all have a resistance value of less than 50mΩ and a resistance tolerance of less than 3%. Moreover, the multilayer connector electronic components of each embodiment all have a bending failure rate of less than 80%, a short-time instantaneous load failure rate of less than 15%, and a gas intrusion failure rate of no more than 20%. This demonstrates that the multilayer connector electronic components of the present invention do indeed possess good current carrying capacity, improve RC lag, and simultaneously have good reliability. In contrast, the thick-film connector electronic component of Reference Example 2, although it also has low component impedance, has a very high bending failure rate, resulting in poor reliability. Furthermore, the manufacturing method of the multilayer connector electronic components of each embodiment is simpler than that of Reference Example 2, and does not require folding or pelletizing steps, nor does it require the use of precious metal raw materials. Therefore, the present invention can also improve product yield and significantly reduce manufacturing costs. Similarly, the multilayer connector electronic component in Example 3, although it also has low component impedance, has a high bending failure rate, resulting in poor reliability.
[0204] Furthermore, when the printing method of the metal conductive layer is the same, comparing the analysis results of Examples 50 to 54, Examples 55 to 59, and Examples 60 to 63, it is found that when the volume of the metal conductive layer contained in the ceramic body increases, the bending failure rate of the multilayer connector electronic component can be reduced. In particular, when the thickness ratio of the metal conductive layer to the ceramic sublayer is 0.28 or higher, the bending failure rate of the multilayer connector electronic component can be reduced to 0. Accordingly, it means that when it encounters stress damage, the risk of failure due to open circuit can be reduced.
[0205] Furthermore, a comparison of the analytical results from Examples 57-III to 57-VI and Examples 70-I to 70-IV shows that when the sintering temperature in the process is low, the multilayer connector electronic components have lower density due to the poor density of their ceramic bodies, resulting in increased bending failure rate, instantaneous load failure rate, and moisture intrusion failure rate.
[0206] As shown in Table 10, the E values of the multilayer connector electronic components in Examples 52, 57, 62, 64 to 68, and 73 to 75 are all above 130 GPa, and the H values are all above 7.9 GPa. Furthermore, their (E / H)1 / 2 values are all greater than 4, indicating that even with almost the same multilayer structure as Reference Example 3, they still possess better mechanical properties and bending resistance. This demonstrates that the multilayer connector electronic components of the present invention, through the combination of specific ceramic materials and multilayer structures, effectively reduce the risk of failure and thus improve their reliability.
[0207] Furthermore, as can be seen from Table 10, the multilayer connector electronic components of the present invention have higher insulation resistance, and therefore, they can have higher electrical safety and reliability.
[0208] Furthermore, as shown in Table 11, regardless of whether the multiple metal conductive layers are divided into multiple groups of interconnecting electrode stacks in the vertical or horizontal direction of the ceramic body, their performance in terms of resistance value and resistance tolerance remains within an acceptable range. However, since the ceramic body simultaneously contains multiple groups of interconnecting electrode stacks, even when the multilayer connector electronic component is damaged by external stress or even becomes open-circuited, the stacked structure of other interconnecting electrode stacks can maintain a short circuit. Therefore, the multilayer connector electronic component of the present invention has excellent bending resistance and reduces its failure risk, thereby improving its reliability.
[0209] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the technical solution of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention shall still fall within the scope of the technical solution of the present invention.
Claims
1. A multilayer connector electronic component, characterized in that, The multilayer connector electronic component includes: A ceramic body having a first end face and a second end face opposite to each other; and Two electrodes, which respectively cover the first end face and the second end face of the ceramic body; The ceramic body is formed by sequentially stacking a ceramic upper cover layer, a ceramic electrode layer, and a ceramic lower cover layer. The ceramic electrode layer includes multiple ceramic sub-layers and a first connecting electrode stack group, which includes multiple metal conductive layers. The ceramic sub-layers and the metal conductive layers are alternately stacked and sandwiched between the ceramic upper cover layer and the ceramic lower cover layer. The metal conductive layers are electrically connected to the two-terminal electrodes. The ceramic material forming the upper ceramic cover layer, the sub-ceramic layer and the lower ceramic cover layer comprises a main powder material and a sintering aid. The main powder material comprises silicate-based microwave dielectric material, barium titanate-based microwave dielectric material, calcium zirconate, strontium zirconate titanate compound or a combination thereof. The molar ratio of barium to titanium in the barium titanate-based microwave dielectric material is less than 1. The conductive metal layer contains a base metal.
2. The multilayer connector electronic component as described in claim 1, characterized in that, This silicate-based microwave dielectric material includes Mg2SiO4, Zn2SiO4, MgCaSi2O6, or combinations thereof.
3. The multilayer connector electronic component as described in claim 1, characterized in that, This barium titanate-based microwave dielectric material contains BaTi4O9 and Ba2Ti9O. 20 Or a combination thereof.
4. The multilayer connector electronic component as described in claim 1, characterized in that, The strontium zirconate titanate compound is represented by formula (1): (Sr a Ca b Ba c (Zr) x Ti y )O3(1); Among them, 0 <a<1,0<b<1,0≤c<1,a+b+c=1;0<x<1,0<y<1,x+y=1。 5. The multilayer connector electronic component as described in claim 1, characterized in that, This base metal contains copper, nickel, or a combination thereof.
6. The multilayer connector electronic component as described in any one of claims 1 to 5, characterized in that, The sintering aid contains glass material.
7. The multilayer connector electronic component as described in claim 6, characterized in that, The glass material comprises Li2O-BaO-SrO-CaO-B2O3-SiO2, Na2O-BaO-ZnO-B2O3-Al2O3-SiO2-CaO-Al2O3-SiO2, MnO-MgO-Al2O3-SiO2, BaO-MgO-Al2O3-SiO2, CaO-MgO-Al2O3-SiO2, BaO-ZnO-B2O3-CaO-Al2O3-SiO2-Cu2O, Na2O-BaO-ZnO-B2O3-Al2O3-SiO2, or combinations thereof.
8. The multilayer connector electronic component as described in claim 7, characterized in that, With a total weight of 100 parts by weight for the main powder material and the sintering aid, the content of the sintering aid can be greater than 0 parts by weight and less than or equal to 15 parts by weight.
9. The multilayer connector electronic component as described in any one of claims 1 to 5, characterized in that, The ceramic material also contains dispersants, binders, plasticizers, or combinations thereof.
10. The multilayer connector electronic component as described in any one of claims 1 to 5, characterized in that, The thickness ratio of each metal conductive layer to each ceramic sublayer is 0.28 to 0.
9.
11. The multilayer connector electronic component as described in any one of claims 1 to 5, characterized in that, Each of the two electrodes includes a first sub-terminal electrode and a second sub-terminal electrode from the inside out; the first sub-terminal electrode covers the first end face and the second end face of the ceramic body and is electrically connected to the metal conductive layer; the second sub-terminal electrode is formed on the outer surface of the first sub-terminal electrode. The first sub-terminal electrode contains copper, and the second sub-terminal electrode contains nickel.
12. The multilayer connector electronic component as claimed in any one of claims 1 to 5, characterized in that, The ceramic electrode layer also includes a second interconnecting electrode stack, which includes multiple metal conductive layers. Looking from the first end face of the ceramic body towards the second end face, the first connecting electrode stack and the second connecting electrode stack are arranged side by side in the horizontal direction of the ceramic body. Each metal conductive layer in the second connecting electrode stack is parallel to each metal conductive layer in the first connecting electrode stack and is spaced apart by a horizontal distance in the horizontal direction of the ceramic body.
13. The multilayer connector electronic component as described in any one of claims 1 to 5, characterized in that, The ceramic electrode layer also includes a second interconnecting electrode stack, which includes multiple metal conductive layers. Looking from the first end face of the ceramic body towards the second end face, the first connecting electrode stack and the second connecting electrode stack are arranged side by side in the vertical direction of the ceramic body; and the uppermost metal conductive layer in the second connecting electrode stack and the lowermost metal conductive layer in the first connecting electrode stack are parallel to each other and spaced apart by a predetermined distance in the vertical direction of the ceramic electrode layer, the predetermined distance being greater than the distance between the metal conductive layers in the first connecting electrode stack.
14. The multilayer connector electronic component as described in any one of claims 1 to 5, characterized in that, The ceramic electrode layer also includes a second connecting electrode stack and a third connecting electrode stack, each of which includes a plurality of metal conductive layers. Looking from the first end face of the ceramic body towards the second end face, the first connecting electrode stack to the third connecting electrode stack are arranged in parallel in the horizontal direction of the ceramic body.
15. The multilayer connector electronic component as described in any one of claims 1 to 5, characterized in that, The ceramic electrode layer also includes a second connecting electrode stack, a third connecting electrode stack, and a fourth connecting electrode stack, each of which includes multiple metal conductive layers. Looking from the first end face of the ceramic body towards the second end face, the first connecting electrode stack and the second connecting electrode stack are arranged side by side in the horizontal direction of the ceramic body, the third connecting electrode stack and the fourth connecting electrode stack are arranged side by side in the horizontal direction of the ceramic body, and the first connecting electrode stack and the third connecting electrode stack are arranged side by side in the vertical direction of the ceramic body.
16. The multilayer connector electronic component as claimed in any one of claims 1 to 5, characterized in that, The ceramic electrode layer also includes a second to a sixth interconnecting electrode stack, each of which includes a plurality of metal conductive layers. Looking from the first end face of the ceramic body towards the second end face, the first to the third connecting electrode stacks are arranged side by side in the horizontal direction of the ceramic body, the fourth to the sixth connecting electrode stacks are arranged side by side in the horizontal direction of the ceramic body, and the first and fourth connecting electrode stacks are arranged side by side in the vertical direction of the ceramic body.
Citation Information
Patent Citations
Terminal structure of chip-like electrical part
JP2007123832A
